Dengue hemorrhagic fever vulnerability assessment in Gorontalo Regency using analytic hierarchy process and geoinformation techniques - Ririn Pakaya; Yanti Hz. Hano; Muhammad Ramdhan Olii (Intelektual Pustaka Media Utama, 2022)
One method of reducing the spread of dengue hemorrhagic fever (DHF) is to provide a map of DHF-prone locations based on spatial analysis. The major way to prevent the spread of DHF is to manage and control its vector by focussing on specific regions of localisation and removing appropriate breeding circumstances. Spatial analysis can detect DHF clusters that are larger than expected based on the underlying data. This research aimed to identify and map DHF vulnerability zones based on many parameters within the scope of the analytical hierarchy and geographical information systems (GIS). We found that the consistency ratio of 0.079 for analytic hierarchy process (AHP) factor weights was judged to be satisfactory. The population density, distance to the road, and distance to health facilities were shown to be the most relevant factors in determining DHF vulnerability. Gorontalo Regency is dominated by low vulnerability classes with an area of 139,493.5 ha or 65.08% of the total area. The GIS-AHP process could be used to assess transmissible DHF vulnerability zonation, which would aid in improving surveillance strategies for DHF and other vector-borne diseases in order to encourage prevention and control actions.